Habitudes de consommation des additifs alimentaires chez la population algérienne « cas des étudiants de la faculté de médecine de Sétif » - KABACHE , Letissia; CHENNIT , Dyhia; KASRI , Laeticia; MAOUCHE , Wassim; ACHOURI , Khaled (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine., 2024)
Context: More and more consumers are being exposed to food additives, especially students in university halls of residence, where the consumption of processed products is replacing ready-made meals at every opportunity. This is a key factor in the spread of the snacking culture, and is often responsible for the increased prevalence of non-Transmissible Diseases (NCDs). Objectives: To assess the characteristics of additive consumption, and to evaluate knowledge of and attitudes towards the International Numbering System (INS) for food additives among students at the Faculty of Medicine in Setif. Methods: A cross-sectional study was carried out on 146 students at the Faculty of Medicine in Setif. A structured questionnaire was designed to assess students' food additive consumption, knowledge and attitudes towards food additives. Results: The survey revealed that the foods most frequently consumed were dairy products, meat products, cereals, cookies, cakes, chicken spices, margarine and jams. And that 76.66% of food products contained at least two food additives, and that citric acid (Sin 330) was present in all selected food categories. It also revealed that students had insufficient knowledge of sin numbers. And that a significant proportion of students did not adopt a correct attitude toward reading nutrition labels. Conclusion: Daily consumption of food additives is linked to a lack of knowledge of Sin numbering and negative attitudes to reading nutrition labels on the part of medical school students, which should be overcome by consumer education programs on food additives.
السياق: يتزايد عدد المستهلكين الذين يتعرضون للمضافات الغذائية كل يوم، وخاصة الطلاب في الإقامات الجامعية، حيث يحل استهلاك المنتجات المصنعة محل الأطباق المطبوخة. وهذا عامل رئيسي في انتشار ثقافة تناول الوجبات الخفيفة وغالبًا ما يكون مسؤولاً عن زيادة انتشار الأمراض غير المعدية. الأهداف: تقييم خصائص استهلاك المضافات الغذائية وتقييم المعرفة والمواقف تجاه نظام الترقيم الدولي للمضافات الغذائية بين طلبة كلية الطب في سطيف. الطرق: أجريت دراسة مقطعية على 146طالبًا في كلية الطب في سطيف. تم تصميم استبيان منظم لتقييم استهلاك الطلاب للمضافات الغذائية ومعرفتهم ومواقفهم تجاه المضافات الغذائية. النتائج: كشف الاستبيان أن الأطعمة الأكثر استهلا ًكا هي منتجات الألبان ومنتجات اللحوم والحبوب والبسكويت والكعك وتوابل الدجاج والسمن النباتي والمربيات. وأن %76.66من المنتجات الغذائية تحتوي على مضافين غذائيين على الأقل، وأن حمض الستريك ( )330 sinكان موجودًا في جميع فئات الأغذية المختارة. كما كشفت أي ًضا أن الطلاب لم يكن لديهم معرفة كافية بالترقيم الدولي للمضافات الغذائية. وأن نسبة كبيرة من الطلاب لم يتبنوا موقفاً صحيحاً في قراءة الملصقات الغذائية. الخلاصة: يرتبط الاستهلاك اليومي للمضافات الغذائية بنقص المعرفة بالترقيم الدولي للمضافات الغذائية وبمواقف سلبية تجاه قراءة الملصقات الغذائية من جانب طلاب كلية الطب في سطيف، وهو ما ينبغي التغلب عليه من خلال إعداد برامج لتثقيف المستهلكين بشأن المضافات الغذائية
Keywords: Sensibilisation; Numéros Sin; Etudiants; Faculté de Médecine; Etiquettes nutritionnelle